Starch-grafted-N-vinylformamide copolymers manufactured by reactive extrusion: synthesis and characterization - Spychaj, T.; Schmidt, B.; Ulfig, K.; Markowska-Szczupak, A. (Polimery, 2012)
Potato starch grafted with N-vinylformamide (NVF) copolymers have been manufactured by reactive extrusion in presence of radical initiators: 2,2'-azobis(2-methylpropionamidine) dihydrogen chloride or 2,2'-azobis(isobutyronitrile). During extrusion the following parameters have been changed: screw speed, temperature profile and initiator type whereas constant weight ratio of the reaction components NVF/starch/water 40:100:34 was kept. Raw copolymerization products have been evaluated by solubility tests in alkali aqueous solution at pH 9.0. Contents of graft copolymer in raw copolymerization products have been determined on a basis of extraction with water/ethanol mixture in the ratio of 70:30. FT-IR spectra of starch-g-NVF copolymers have been recorded and polysaccharide chains were subjected to enzymatic degradation using a- and b-amylases. Residual poly(N-vinylformamide) (PNVF) chains were characterized via gel permeation chromatography. Molecular weights of grafted PNVF were compared with literature data of polyacrylamide chains grafted on potato starches.